Robust T Cell Immunity in Convalescent Individuals with Asymptomatic or Mild COVID-19 - Sekine, Takuya; Perez-Potti, André; Rivera-Ballesteros, Olga; Strålin, Kristoffer; Gorin, Jean-Baptiste; Olsson, Annika; Llewellyn-Lacey, Sian; Kamal, Habiba; Bogdanovic, Gordana; Muschiol, Sandra; Wullimann, David J; Kammann, Tobias; et al. (Cell, 2020)
SARS-CoV-2-specific memory T cells will likely prove critical for long-term immune protection against COVID-19. Here, we systematically mapped the functional and phenotypic landscape of SARS-CoV-2-specific T cell responses in unexposed individuals, exposed family members, and individuals with acute or convalescent COVID-19. Acute-phase SARS-CoV-2-specific T cells displayed a highly activated cytotoxic phenotype that correlated with various clinical markers of disease severity, whereas convalescent-phase SARS-CoV-2-specific T cells were polyfunctional and displayed a stem-like memory phenotype. Importantly, SARS-CoV-2-specific T cells were detectable in antibody-seronegative exposed family members and convalescent individuals with a history of asymptomatic and mild COVID-19. Our collective dataset shows that SARS-CoV-2 elicits broadly directed and functionally replete memory T cell responses, suggesting that natural exposure or infection may prevent recurrent episodes of severe COVID-19.